Status antioksidan dan oksidatif laki-laki yang mengalami kegemukan dengan pemberian minuman rosela ungu - Sriyanti, Sriyanti; Damayanthi, Evy; Anwar, Faisal (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2019)
Background : Rosela (Hibiscus sabdariffa L.) is an anthocyanin-rich plant that has good antioxidant capacity. However, the utilization was limited to red roselle, while previous studies showed that anthocyanin content was found to be higher in the thick roselle.therefore, this is an opportunity to develop purple roselle products as a preventive effort for degenerative diseases in men with fatness. Subjects in this study were male by considering the effect of estrogen on women which could play a role in suppressing oxidative stress.Objectives : This study aimed to analyze antioxidant (SOD/Superoxide dismutase) and oxidative status (MDA/malondialdehyde) level in obese adult men after administration of purple rosela drinks. Methods : This study was quasi-experimental with pre-post test. Eighteen obese subjects in the security unit were divided into two groups, namely the intervention group and control group. Intervention group (n = 9) was given purple rosela drinkin the amount of 480 mL/day, while the control group (n = 9) was given an equivalent amount of purple rosela drink without rosela. The subjects were daily administered for 6 weeks. Characteristic, anthropometric, food consumption and blood sample data were collected at the beginning and end of the intervention. Data analysis was performed by descriptively, paired t-test, independent t-test, ANCOVA.Results : The analysis showed that purple rosela drink tend to increase SOD levels (0.45 ± 0.14; 1.35 ± 0.71; p-value = 0.008) but this value was not significantly different from the control group (p-value = 0.128). MDA levels did not significantly different between the intervention and control groups (0.025 ± 0.083;-0.125 ± 0.60; p-value = 0.473).Conclusion : These results showed that administering 480 ml of purple rosela drink did not improve antioxidant and oxidative status in obese adult men.